2020
DOI: 10.1016/j.ebiom.2020.102724
|View full text |Cite
|
Sign up to set email alerts
|

Precise pulmonary scanning and reducing medical radiation exposure by developing a clinically applicable intelligent CT system: Toward improving patient care

Abstract: Background: Interstitial lung disease requires frequent re-examination, which directly causes excessive cumulative radiation exposure. To date, AI has not been applied to CT for enhancing clinical care; thus, we hypothesize AI may empower CT with intelligence to realize automatic and accurate pulmonary scanning, thus dramatically decrease medical radiation exposure without compromising patient care. Methods: Facial boundary detection was realized by recognizing adjacent jaw position through training and testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…To date, many CT imaging devices have deployed computer vision techniques to track patients, and measure their position, shape, height and width contours using 3D optical or infrared cameras, and to automatically align the anatomical location of the patients with the isocenter of the bore. The AI-enabled U-HAPPY (United imaging Human Automatic Planbox for PulmonarY) scanning CT designed by Wang et al presents one example of such automatic and accurate CT scanning technologies [183]. In that study, the performance of automatic localization and radiation doses were evaluated in three scenarios, i.e., fully automatic, semi-automatic, and manual scanning, and it demonstrated that the fully automatic scenario significantly outperformed the others (Fig.…”
Section: A Tele-imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many CT imaging devices have deployed computer vision techniques to track patients, and measure their position, shape, height and width contours using 3D optical or infrared cameras, and to automatically align the anatomical location of the patients with the isocenter of the bore. The AI-enabled U-HAPPY (United imaging Human Automatic Planbox for PulmonarY) scanning CT designed by Wang et al presents one example of such automatic and accurate CT scanning technologies [183]. In that study, the performance of automatic localization and radiation doses were evaluated in three scenarios, i.e., fully automatic, semi-automatic, and manual scanning, and it demonstrated that the fully automatic scenario significantly outperformed the others (Fig.…”
Section: A Tele-imagingmentioning
confidence: 99%
“…12. Intelligent CT performance testing, (a-d) full automatic results, (e-h) manual results, and (i-j) comparison of the scanning length error and radiation dose among the full, semi and manual scenarios [183]. been used in Wuhan during the COVID-19 outbreak, has prevented cross infections among medical staff and infected patients, and provided doctors a robust foundation to work on.…”
Section: A Tele-imagingmentioning
confidence: 99%
“…By virtue of 3D visual sensors, AI can identify the pose and shape of patients and realize an automated contactless image acquisition work ow. Yang Wang et al (2020) reported that U-HAPPY (United imaging Human Automatic Planbox for PulmonarY) CT has a function with automatic positioning and scanning, which helps to reduce the radiation dose [6]. Booij et al [7] and Saltybaeva et al [8] also reported the patient centering accuracy in CT using 3D cameras that relies on deep neural network for image contouring.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of visual sensors, AI can identify the pose and shape of patients and realize an automated contactless image acquisition work ow. Yang Wang et al (2020) reported that U-HAPPY (United imaging Human Automatic Planbox for PulmonarY) CT has a function with automatic positioning and scanning, which helps to reduce the radiation dose [6]. Recently, GE Healthcare also introduced a Revolution Maxima CT, which relies on deep learning algorithms and real-time depth sensing technology to center patients, locate desired anatomies and perform scan automatically.…”
Section: Introductionmentioning
confidence: 99%